Finding Aids and Networked Biography: Stuart Hall and the Centre for Contemporary Cultural Studies - Katherine Parsons (European Journal of Life Writing)
Finding aids – tools to help researchers locate and understand archival materials – are rich with biographical information: in archival descriptions, we find personal milestones stated alongside traceable genealogies of ideas and associations between people and institutions. A pilot project at the University of Birmingham tested digital methods for distilling this information as a means to life writing; this paper reports on its findings. The pilot project involved extracting networked data from finding aids associated with Stuart Hall (1932-2014) – a founding figure of cultural studies – and the Centre for Contemporary Cultural Studies (CCCS; 1964-2002). A tool was developed to capture data around the movement, meetings, connections, and output of individuals and groups. The project aimed to visualise Hall’s life (people and entities he worked with, events he attended, etcetera) and the institutional ‘life’ of the CCCS (flow of finance, members, and influences). This paper outlines challenges faced by the project team and steps taken to circumvent them, and considers matching the form of digital representation to the distinctive pedagogical approach advocated by Hall and the CCCS. With the particularity of this dataset in mind, this paper discusses how digital methods can be applied to extract and organise finding aid data as a means of framing Hall’s biography.